PERSAMAAN HAK JABATAN FUNGSIONAL PAMONG BELAJAR DAN GURU MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL - Thabrani, Eddy Purnama, Iskandar A.Gani (Jurnal Ilmu Hukum, 2014)
Abstract: Preamble to the Constitution of the Republic of Indonesia Year 1945 mention one goal is the formation of the intellectual life of the nation state. One of the most important components to achieving these goals is the availability of teaching staff. Law Number 20 Year 2003 on National Education System, consisting of teacher educators, lecturers, pamong belajar, tutors, trainers or other terms. The purpose of this study is to analyze and explain the rules of law relating to pamong belajar as educators in the implementation of non-formal education and to assess the consequences of functional positions juridical pamong belajar in the implementation of non-formal education in the national education system. This study used a descriptive approach and analytical preskriftif, that is by the depiction of the existence and rights of pamong belajar as educators in the implementation of non-formal education. The study concluded that pamong belajar an educator who is recognized by the Law on National Education System. Pamong belajar not to get the rights acquired as a teacher educator. Functional position pamong belajar not received the same treatment with the teacher. There is no specific law or regulation (Qanun) that regulate and fulfill the rights in the functional position of pamong belajar that compared to the professorship that has successfully defined in Law No. 14 Year 2005 on Teachers and Lecturers, where the enactment the law allows a teacher certified by the profession as well as improvements in capacity and welfare arrangements. It is recommended to the Government to change and add to Article 1 paragraph 1 of Article figure 1a into the sound of